Coming to work while sick: An economic theory of presenteeism with an application to German data - Boris Hirsch; Daniel Lechmann; Claus Schnabel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Presenteeism, i.e. attending work while sick, is widespread and associated with significant costs. Still, economic analyses of this phenomenon are rare. In a theoretical model, we show that presenteeism arises due to differences between workers in the disutility from workplace attendance. As these differences are unobservable by employers, they set wages that incentivise sick workers to attend work. Using a large representative German data set, we test several hypotheses derived from our model. In line with our predictions, we find that stressful working conditions and bad health status are positively related to presenteeism. Better dismissal protection, captured by higher tenure, is associated with slightly fewer presenteeism days, whereas the role of productivity and skills is inconclusive.
Keywords: I19; J22; J29; 330